Microstructure and Mechanical Properties of Novel Quasibinary Al-Cu-Yb and Al-Cu-Gd Alloys - Sayed Amer; Ruslan Barkov; Andrey Pozdniakov (Metals, 2021)
Microstructure of Al-Cu-Yb and Al-Cu-Gd alloys at casting, hot-rolled -cold-rolled and annealed state were observed; the effect of annealing on the microstructure was studied, as were the mechanical properties and forming properties of the alloys, and the mechanism of action was explored. Analysis of the solidification process showed that the primary Al solidification is followed by the eutectic reaction. The second Al8Cu4Yb and Al8Cu4Gd phases play an important role as recrystallization inhibitor. The Al3Yb or (Al, Cu)17Yb2 phase inclusions are present in the Al-Cu-Yb alloy at the boundary between the eutectic and aluminum dendrites. The recrystallization starting temperature of the alloys is in the range of 250–350 °C after rolling with previous quenching at 590 and 605 °C for Al-Cu-Yb and Al-Cu-Gd, respectively. The hardness and tensile properties of Al-Cu-Yb and Al-Cu-Gd as-rolled alloys are reduced by increasing the annealing temperature and time. The as-rolled alloys have high mechanical properties: YS = 303 MPa, UTS = 327 MPa and El. = 3.2% for Al-Cu-Yb alloy, while YS = 290 MPa, UTS = 315 MPa and El. = 2.1% for Al-Cu-Gd alloy.